From Robot to Virtual Doppelganger: Impact of Visual Fidelity of Avatars Controlled in Third-Person Perspective on Embodiment and Behavior in Immersive Virtual Environments - Gorisse, Geoffrey; Christmann, Olivier; Houzangbe, Samory; Richir, Simon (Frontiers in Robotics and AI, 2019)
This study presents the second phase of a series of experiments investigating the impact of avatar visual fidelity on the sense of embodiment and users' behavior in immersive virtual environments. Our main focus concerns the similarity between users and avatars, a factor known as truthfulness. Our experiment requires the participants to control three avatars using a third-person perspective: a robot, a suit and their virtual doppelganger (virtual representation of the self). In order to analyze users' reactions and strategies, each task of the scenario of the virtual reality application can potentially affect the integrity of their characters. Our results revealed that ownership, one of the three factors of the sense of embodiment, is higher for the participants controlling their self-representation than with abstract representations. Furthermore, avatar visual fidelity seems to affect users' subjective experience, half of the panel reported having different behavior depending on the controlled character. Abstract representations allow the users to adopt more risky behaviors, while self-representations maintain a connection with the real world and encourage users to preserve the integrity of their avatar.